O tratamento de dados de crianças e adolescentes para fins publicitários e a tutela coletiva - Barbosa, Liliane Mageste (2023)
Technological evolution has significantly influenced the Law, giving rise to new interests that must be conformed to the legal system. In the context of Consumer Law, advertising was severely impacted by the information society, enabling the increasingly personalized and effective targeting of advertisements based on the processing of personal data. At the time that the protection of personal data was recently incorporated into article 5, LXXIX of the Brazilian Federal Constitution as a fundamental right (Constitutional Amendment n. 115/2022), it is questioned whether there is specialized treatment to be given to children and adolescents, in especially when they are used for advertising purposes. Futhermore, tha class action is analyzed under the focus of adequacy for the defense of the right in question and the legitimacy for conducting the collective dispute